Analysis of The Development of Non-Cognitive Assessment Instrument to Support Online History Learning in Jambi City High School - Willy Cahyadi; Dian Aswita; Tri Zahra Ningsih (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research is important to do because (1) there is a lack of an accurate non-cognitive skill assessment tool to assess non-cognitive skills in online learning; (2) it is difficult for teachers to measure students' cognitive skills during online learning due to the limited assessment tools available; and (3) only a few instruments have been developed to measure non-cognitive skills in social science learning, particularly history learning. Based on this gap, it's critical to examine the creation of non-cognitive skills evaluation instruments, particularly for use in online history classes. We collect data through surveys and questionnaires, answering questions. The study's subjects were Jambi City Senior High School teachers, a group of 15 from five different schools. Proportional Random Sampling Strategy is the sampling technique used in this study. An observation sheet and a questionnaire sheet were utilized as research instruments in this study. The questionnaire sheet consists of a questionnaire sheet to collect data on non-cognitive skills. The results of the study were examined using descriptive statistical methods. Non-cognitive skills are critical to acquire in online learning, according to the findings of the study. According to the research, 81.67% of teachers strongly believe that non-cognitive skills have an impact on student success. Non-cognitive qualities including discipline, independence, time management, teamwork, motivation, and technological skills are identified by 84.44 % of teachers as having a significant impact on the success of online learning. According to the teacher, 93.3% strongly agreed to create an assessment instrument to test this skill. The importance of non-cognitive instrument development is evident from the preceding discussion.